Electromagnetic Force Calculation of Conductor Plate Double Halbach Permanent Magnet Electrodynamic Suspension - Chen, Yin; Zhang, Kunlun (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In order to solve the problem of high drag force in traditional Permanent Magnet Electrodynamic Suspension (PM-EDS) and increase the levitation-drag force ratio, this paper proposes a new suspension system composed of conductor plates and a double Halbach permanent magnet array, and calculates its electromagnetic force. The eddy current distribution equation for the conductor plate and the analytic calculation formula for the electromagnetic force of the device are derived by solving the differential equations for the magnetic vector potential in space. Verifying the analytic method using the finite element method, the maximum and mean relative errors of the results were calculated to be 4% and 1.7%, respectively. This paper also compares the levitation-drag force ratio of the new suspension system with that of the traditional system and concludes that the new system can substantially reduce the drag force and power loss.